0404 A Novel Approach to Sleep Disturbances in the Inpatient Psychiatric Setting: Video-Based Cognitive Behavioral Therapy for Insomnia. (27th April 2018) - Brock, M S; Mysliwiec, V; Germain, A; Fullam, T; Xuan, D; Sidari, L; Cleaves, E; Jackson, C; Willis, A; Park, J; Mansfield, J; Weidlich, C; et al.
Abstract: Introduction: Sleep disturbances are common in patients hospitalized for psychiatric disorders. Inpatient psychoeducation/therapy does not focus on sleep complaints. Standard treatment consists of pharmacologic therapy and there is limited data on cognitive behavioral therapy for insomnia (CBT-I) in this population. The purpose of this study was to assess the efficacy of video-based CBT-I on a psychiatric inpatient unit compared to treatment as usual (TAU). Methods: Patients admitted to a psychiatric unit for the first time with any behavioral medicine diagnosis and a sleep disturbance were eligible. Participants were randomly assigned to receive TAU (handout on appropriate sleep practices) or the intervention, which consisted of daily one-hour sessions. In each session, participants viewed an entertaining professionally made video-based CBT-I lesson (6 novel videos encompassing all CBT-I components) followed by group discussion. Participants completed sleep questionnaires including the Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI) at intake and discharge along with a daily sleep diary. Results: At the time of analysis, 29 participants had enrolled with 22 receiving the intervention and 7 TAU. The intervention group was mostly male (n=14, 63.6%) and relatively young (median age 20). The average ISI decreased from 15 (SD=6.9) to 12.2 (SD=7.5; t(21)=2.58, p=0.017) and average PSQI decreased from 10.9 (SD=4.6) to 8.8 (SD=4.1; t(21)=3.0, p=0.007) in the intervention group. Reported mean sleep onset time decreased by 11.07 minutes (SD=19.51; t(21)=-2.66, p=0.015), total sleep time increased by 1.33 hours (SD=1.44; t(21)=4.33, p=0.0003), and sleep efficiency improved by 11% (SD=16; t(21)=3.25, p=0.004). Patient feedback regarding the intervention was overwhelmingly positive. The TAU group had some improvement in sleep, but no changes met statistical significance. Conclusion: Video-based CBT-I improves insomnia symptoms and sleep quality in psychiatric inpatients. Compared to traditional CBT-I that is administered in-person but often unavailable, this novel modality has the potential to improve sleep in a wide variety of clinical settings. Support (If Any): Air Force Medical Support Agency (AFMSA) Intramural Research Development Test & Evaluation Funds (Contract #W911QY-11-D-0055 0012) supported this project.